2015
DOI: 10.1016/j.anorl.2013.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Dysphagia after radiotherapy: State of the art and prevention

Abstract: Adjuvant radiotherapy after surgery or exclusive radiotherapy, with or without concurrent chemotherapy is a valuable treatment option in the great majority of patients with head and neck cancer. Recent technical progress in radiotherapy has resulted in a decreased incidence of xerostomia. Another common toxicity of radiotherapy is dysphagia, which alters the nutritional status and quality of life of patients in remission. The objective of this review is to describe the physiology of swallowing function, the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 50 publications
0
17
0
3
Order By: Relevance
“…In an earlier study among patients with OPC with advanced stage treated with concurrent RT and chemotherapy, feeding tube use had the maximum impact on QOL (−30 points compared to controls) evaluated by SF36 and HNQOL. 46 Late LCNP cases also had significantly higher rates of aspiration pneumonia (32.3% LCNP vs 2.0% no LCNP), which support association with high dysphagia-related morbidity. Similarly, a study using SEER data among patients with HNC treated with chemoradiation reported 23.8% 5-year rates of aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…In an earlier study among patients with OPC with advanced stage treated with concurrent RT and chemotherapy, feeding tube use had the maximum impact on QOL (−30 points compared to controls) evaluated by SF36 and HNQOL. 46 Late LCNP cases also had significantly higher rates of aspiration pneumonia (32.3% LCNP vs 2.0% no LCNP), which support association with high dysphagia-related morbidity. Similarly, a study using SEER data among patients with HNC treated with chemoradiation reported 23.8% 5-year rates of aspiration pneumonia.…”
Section: Discussionmentioning
confidence: 66%
“…High rates of gastrostomy dependence among LCNP cases again support a high prevalence of dysphagia in this population. In an earlier study among patients with OPC with advanced stage treated with concurrent RT and chemotherapy, feeding tube use had the maximum impact on QOL (−30 points compared to controls) evaluated by SF36 and HNQOL . Late LCNP cases also had significantly higher rates of aspiration pneumonia (32.3% LCNP vs 2.0% no LCNP), which support association with high dysphagia‐related morbidity.…”
Section: Discussionmentioning
confidence: 73%
“…Bei 40 -80 % führt diese neben Mangelernährung zu Aspirationen. Im Rahmen eines multidisziplinären Ansatzes mit vor allem neuen Bestrahlungstechniken zur Präven-tion sowie rehabilitativ erlernten Schlucktechniken und adaptierter Kost kann man das Management optimieren [45]. In einer randomisierten kontrollierten Studie erhielten die Patienten zusätzlich Omega-3-Fettsäuren (EPA/DHA) im Rahmen der Gabe von 500 ml Supportan ® additiv zur normalen Standardernährung.…”
unclassified
“…The extensive toxicities experienced by patients will be discussed in greater detail in Section Cohen et al, 2016;National Comprehensive Cancer Network, 2013;Schindler et al, 2015). There is a large evidence base supporting the benefit of SP involvement before, during and after (C)RT to optimise swallowing outcomes (Messing et al, 2019;Murphy & Gilbert, 2009;Russi et al, 2012;Servagi-Vernat et al, 2015;Wall, Cartmill, Ward, Hill, Isenring, & Porceddu, 2016). Speech pathology in HNC will be discussed in greater detail in section 1.4.…”
Section: Head and Neck Cancer Managementmentioning
confidence: 99%